EFFICACY OF MADHYAMA PANCHAMOOLA CHURNA IN KSHEENASHUKRA (OLIGOSPERMIA) - A CASE REPORT (AYUSHDHARA, 2021)
Male infertility is a condition in which male inability to result pregnancy in fertile female partner. It accounts to 40-50% infertility. It is due to low sperm concentration, poor sperm motility and abnormal morphology of sperm etc. Ayurveda classical texts explained male fertility defects under eight types of Shukra dusti. Ksheenashukra is one among Shukradusti affecting lowered state of sperm concentration and it can be correlated to Oligospermia. There are number of single and combination of drugs mentioned to this condition. In present case study, a subject of 32 year old male attended the free male infertility medical camp with complaints of unable to conceive her partner even after unprotected intercourse since 4 years of married life. Semen analysis report reveals that low sperm count and low motility. This case was treated with Madhyama panchamoola churna along with Ksheera for 3 months. After the course of the treatment semen volume, sperm count, sperm motility, sperm morphology, total testosterone and sexual activity were enhanced. His partner conceived during the course of the treatment. The findings in study revealed that Madhyama panchamoola churna in Oligospermia with no adverse effects highlight the scope of Ayurveda medicine in male infertility disorders.